A GIS‐based approach for delineating suitable areas for cage fish culture in a lake. Issue 2 (13th April 2021) - Mulanda Aura, Christopher; Musa, Safina; Nyamweya, Chrisphine S.; Ogari, Zachary; Njiru, James M.; Hamilton, Stuart E.; May, Linda
Abstract: We present a GIS‐based approach to the delineation of areas that have different levels of suitability for use as tilapia cage culture sites the Kenyan part of Lake Victoria, Africa. The study area was 4, 100 km 2 . The method uses high‐resolution bathymetric data, newly collected water quality data from all major fishing grounds and cage culture sites, and existing spatial information from previous studies. The parameters considered are water depth, water temperature, levels of dissolved oxygen, chlorophyll‐ a concentrations, distances to the lake shoreline and proximity to other constraints on cage culture development. The results indicated that the area most suitable for fish cages comprised about 362 km 2, or approximately 9% of the total area; the remaining 91% (i.e., 3, 737 km 2 ) was found to be unsuitable for tilapia cage culture. We conclude that the successful implementation of this approach would need stakeholder involvement in the validation and approval of potential sites, and in the incorporation of lake zoning into spatial planning policy and the regulations that support sustainable use while minimising resource use conflicts. The results of this study have broader applicability to the whole of Lake Victoria, other African Great Lakes, and any lakes in the world where tilapia cage culture already occurs or may occur in the future.